2017
DOI: 10.1038/s41598-017-07921-2
|View full text |Cite|
|
Sign up to set email alerts
|

Dipeptidyl peptidase-4 inhibitors and cancer risk in patients with type 2 diabetes: a meta-analysis of randomized clinical trials

Abstract: Some recent studies have suggested that the use of dipeptidyl peptidase-4 inhibitors (DPP4i) is associated with cancer development. However, some other studies suggest no such association. The aim of the present study was to evaluate the effect of DPP4i on the risk of developing cancers. The electronic databases PubMed, Medline, EMBASE, Web of Science and Cochrane Library and the clinical trial registry were searched for published and unpublished randomized clinical trials on humans. Eligible studies were RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 57 publications
(44 reference statements)
2
48
0
Order By: Relevance
“…Since the first DPP-4 inhibitor sitagliptin (trade name, Januvia) was approved by the U.S. FDA in 2006, more than one hundred meta-analyses have focused on the efficacy and safety of DPP-4-inhibitors [41][42][43][44][45][46]. Nevertheless, whether or not DPP-4 inhibitors will influence the T cell immune homeostasis or in turn decrease the risk of autoimmune disease in human has not reached a consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first DPP-4 inhibitor sitagliptin (trade name, Januvia) was approved by the U.S. FDA in 2006, more than one hundred meta-analyses have focused on the efficacy and safety of DPP-4-inhibitors [41][42][43][44][45][46]. Nevertheless, whether or not DPP-4 inhibitors will influence the T cell immune homeostasis or in turn decrease the risk of autoimmune disease in human has not reached a consensus.…”
Section: Discussionmentioning
confidence: 99%
“…All these trials demonstrate that gliptins do not increase tumor risk in T2DM patients. Zhao performed a meta-analysis with a total of 72 trials enrolled and no significant associations are detected between the use of gliptins and cancer development (Zhao et al, 2017), indicating the safety rather than benefits of gliptins in tumor.…”
Section: Dpp4/cd26 Inhibition On Cancermentioning
confidence: 99%
“…Further, in a pooled analysis of data from 25 clinical trials on 14 611 diabetes patients randomized to use either sitagliptin (a DPP‐4 inhibitor) or a control treatment (placebo, metformin, pioglitazone, a sulfonylurea medication, insulin, or metformin with rosiglitazone or pioglitazone) for between 12 weeks and 2 years, similar incidence rates of overall cancer in the two groups were observed (rate difference: −0.05 events per 100 person‐years (95% CI: −0.41, 0.30)) . Finally, authors of a recent meta‐analysis of results from a total of 72 RCTs on DPP‐4 inhibitors reported that the estimated risk ratio for overall cancer was 1.01 (95% CI: 0.91, 1.28) when the control treatment included the use of placebo, sulfonylureas, or metformin, while when the analysis was restricted to studies with sulfonylureas as the control treatment, the corresponding result was 1.40 (95% CI: 0.99, 1.96) …”
Section: Discussionmentioning
confidence: 91%
“…31 Finally, authors of a recent meta-analysis of results from a total of 72 RCTs on DPP-4 inhibitors reported that the estimated risk ratio for overall cancer was 1.01 (95% CI: 0.91, 1.28) when the control treatment included the use of placebo, sulfonylureas, or metformin, while when the analysis was restricted to studies with sulfonylureas as the control treatment, the corresponding result was 1.40 (95% CI: 0.99, 1.96). 32 In our primary analyses, we presumed the "class effect" of incretin-based medications on the risk of cancer. This presumption is supported by the fact that DPP-4 inhibitors and GLP-1 receptor agonists share at least some pathways potentially underlying these medications' hypothesized effect on cancer risk, 33 but it also seems to be supported by results from a CPRD-based study by Hicks et al, who…”
Section: Discussionmentioning
confidence: 99%